The Centrality and Metamorphoses of Work in the 21st Century: Precarious Work, Class Consciousness and Resistance from the Perspective of Emancipation - Gomes Cardoso, Franci; Fonsêca Silva, Karênina (Pontifícia Universidade Católica de São Paulo, 2021)
This article presents partial results of research on the centrality of work and its changes in the current century. It discusses work as a founding category of the social being, the genesis of the sociability process, insofar as it is a natural and eternal condition of human life. It reaffirms that, in the context of precarious work, work does not lose its centrality to human existence with regard to social relations. It reflects on the capacity of man, starting from work, to transform nature, himself and others, and to create possibilities to break with the strangeness and imprisonments engendered in the relations of domination between capital and labor through resistance struggles seeking emancipation.